Open Access Repositories and Policies in Turkish Universities - Sarı, Özge; Doğan, Güleda (Information World, 2023)
Since the early 2000s, Türkiye has witnessed significant advancements in Open Access (OA) repositories, primarily in terms of quantitative aspects. Nevertheless, notable challenges persist concerning the quality of both archives and their contents. This research investigates the current state of Turkish universities’ OA repositories and policies. It relies on data collected from university and repository websites over a span of about two years (2019-2020), divided into three consecutive periods (June 2019, March 2020, November 2020). The significance of this time interval lies in the CoHE’s efforts towards university OA repositories during this time. We compared the data collected for the three periods with the data collected by CoHE based on university declarations for similar periods, resulting in a two-way analysis. According to the findings, there is an increase in the number of university OA repositories and records in these repositories, albeit not systematically. Universities that were established earlier have a greater presence of OA repositories than those established later, regardless of whether they are public or foundation universities. On the other hand, the number of records in university OA repositories is not affected by the university’s age, type, or the presence of an OA policy, even if such a policy is mandatory. This scenario indicates that the AE policies lack sufficient functionality. When compared to CoHE data, all three periods had more repositories, but the most significant difference was seen in the number of mandatory OA policies. According to CoHE data, the number of mandatory OA policies is significantly higher than what was found in the collected data, indicating a lack of knowledge among repository managers despite the numerous national events on OA. This study distinguishes itself from related previous research by examining the current situation of OA repositories in Türkiye across three consecutive periods, using data collected directly from primary sources, comparing this data with university declaration-based data from CoHE, and analyzing the contents of OA policies.
Keywords: Open access; open access repository; university open access repositories; open access policy; universities; Council of Higher Education; CoHE